ANALISIS EFEKTIVITAS PENDAPATAN HOTEL DAN WISATA KUSUMA AGRO SEBELUM, PADA SAAT DAN NEW NORMAL PANDEMI COVID-19 (Studi Kasus Pada PT. Kusuma dinasasri Wisata Jaya) - Nofita Pratiwi; Anik Malikah; Afifudin Afifudin (Universitas Islam Malang, 2022)
This study aims to determine and analyze the effectiveness of Kusuma Agro Hotel and Tourism Revenues Before, During and New Normal Covid-19 Pandemic. By using secondary data in the form of hotel and tourism income reports using data collection methods including data reduction, data presentation in the form of narratives and tables using Excel application tools. The results of this study indicate that (1) The Effectiveness Level of Hotel Revenue Before the Covid-19 virus was 90% included in the criteria of Quite Effective. (2) Hotel Revenue Level during Covid-19 is 63% Included in the Less Effective Criteria. (3) The Effectiveness Level During the New Normal Covid-19 Hotel Revenue is 78% included in the Less Effective criteria (4) The Effectiveness Level of Tourism Revenue Before the Covid-19 virus was 112% included in the Very effective criteria (5) The current tourism income effectiveness level Covid-19 is 88% included in the Quite Effective criteria (6) Effectiveness Level During the New Normal Covid-19 Tourism income is 74% included in the Less Effective criteria.Keywords: Effectiveness, Effectiveness Ratio, COVID-19, New